Niewydane tłumaczenie epigramów Sarbiewskiego, czyli uwagi o działalności przekładowej prof. Zofii Abramowiczówny - Witczak, Krzysztof Tomasz (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
The paper describes a Polish translation of M. K. Sarbiewski’s Latin epigrams made by Zofia Abramowicz (1906–1988) during the interwar period. These epigrams (partially preserved) were prepared to be published in 1939 or 1940 by Prof. Ryszard Ganszyniec in his „Filomata” Press. Abramowicz’s translational work seems to be a part of history of the classical philology in Poland.